(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
In this paper, a new approach has been developed to create virtual dress based on different body types. A 3D scan data of 232 Chinese females were analyzed. Firstly, samples were classified into four categories which were Torso Volume Index (TVI), slender, average, full and heavy. Secondly, 3D body frame, including 10 feature cross-sections extracted from the scan data, was defined and preprocessed. After that, the average data of 3D body frame in each body type group was calculated and a comparative analysis of the feature measurements among the four average body frames was performed. Finally, a shape deformation algorithm was presented to modify the template model according to four average body frames. And surface fitting is implemented by using NURBS technology. In conclusion, the research has created four mannequins representing the average body shape of each group subjects. The results can contribute to the future study on customizing digital mannequins for 3D virtual apparel design system, according to the body shape of target population.